Process Improvement: Addressing Attrition from the Uniformed Services University of the Health Sciences Nurse Anesthesia Program. - Tyler Wilson, John (AANA Journal, 2015)
This retrospective cohort study examined the Uniformed Services University of the Health Sciences Registered Nurse Anesthesia program to identify reasons for high attrition rates. Relevant data were examined for 180 students enrolled in classes from 2005 through 2011. During that period, 40 students were dismissed or disenrolled, with the highest attrition rate (35%) occurring in the class of 2010. Evidence from this investigation indicates students who completed the program were younger, earned higher grade point averages while completing their undergraduate bachelor of science in nursing, and achieved higher analytic and total Graduate Record Examination scores than did students who withdrew or were dismissed. Gender differences were noted, as a greater proportion of women completed the program compared with men. Personal, family, and other issues frequently overlapped, with academic performance problems leading to attrition. Based on these findings, a number of important changes were made in the admission process to the USUHS RNA program and in the nonaca-demic mentoring and assistance offered to students.